The last letter from your lover eaudiobook A novel. - Moyes, Jojo (Penguin Audio, 2011)
Now a major motion picture streaming on Netflix starring Felicity Jones, Shailene Woodley, Callum Turner, Nabhaan Rizwan and Joe Alwyn From the #1 New York Times bestselling author of The Giver of Stars and the forthcoming Someone Else's Shoes , a sophisticated, page-turning double love story spanning forty years It is 1960. When Jennifer Stirling wakes up in the hospital, she can remember nothing-not the tragic car accident that put her there, not her husband, not even who she is. She feels like a stranger in her own life until she stumbles upon an impassioned letter, signed simply "B", asking her to leave her husband. Years later, in 2003, a journalist named Ellie discovers the same enigmatic letter in a forgotten file in her newspaper's archives. She becomes obsessed by the story and hopeful that it can resurrect her faltering career. Perhaps if these lovers had a happy ending she will find one to her own complicated love life, too. Ellie's search will rewrite history and help her see the truth about her own modern romance. A spellbinding, intoxicating love story with a knockout ending, The Last Letter from Your Lover will appeal to the readers who have made One Day and The Guernsey Literary and Potato Peel Pie Society bestsellers.